PRÁTICAS DE LABORATÓRIO - O ELEVADOR HIDRÁULICO - Barros, Marcelo Alves; Farias, Adriel Antônio; Rosa, Amarildo; Giacomassi, Ana Paula; de Almeida, Fabiana Ribeiro; Hirata, Fábio Henrique; da Silva, Fábio Ramos; Sanches, Mônica Bordim; Arroteia, Mônica Yara; Barbosa, Roberto Gonçalves (Arquivos do Mudi, 2013)
Os autores apresentam um esperimento que simila um elevador hidráulico.